The great ceo within : the tactical guide to company b - Mochary, Matt; MacCaw, Alex; Talavera, Misha (Ascent Audio, 2021)
Matt Mochary coaches the CEOs of many of the fastest-scaling technology companies in Silicon Valley. With The Great CEO Within, he shares his highly effective leadership and business-operating tools with any CEO or manager in the world. Learn how to efficiently scale your business from startup to corporation by implementing a system of accountability, effective problem-solving, and transparent feedback. Becoming a great CEO requires training. For a founding CEO, there is precious little time to complete that training, especially at the helm of a rapidly growing company. Now you have the guidance you need in one book.